RESPONS TEKNOLOGI DEPURASI TERHADAP KADAR TIMBAL (Pb) DALAM KERANG HIJAU HASIL PEMBUDIDAYAAN DI PANTAI BANYUURIP KECAMATAN UJUNG PANGKAH KABUPATEN GRESIK - Aminin Aminin; Andi Rahmad Rahim; Nur Maulida Safitri (Jurnal Perikanan Pantura (JPP), 2020)
The decrease of green mussel production in 3 years (2018 – 2020) was suspected to Pb levels on the whole organ of green mussels, which estimated to 0.7 ppm, in Banyuurip village, Ujung Pangkah, Gresik Regency. The expansion of industrial or domestic (household) activity was claimed to contribute a magnificent waste in the water. The purpose of this study was to analyze Pb levels on the whole organ of green mussles before and after the depuration. This research was implemented in Gayam, Soko Village, Glagah Sub-District, Lamongan Regency. Green mussel samples was taken from Banyuurip beach, where the green mussels culture was done. Then, 10 kg of green mussels was added to several container in size 150 L for depuration procedure. The main parameter in this research was the Pb level on the whole organ of green mussels and water media, and the other parameter was water quality (DO, pH, salinity, temperature and amonia). After performed this research, we expected to give information of depuration technology respond against Pb reduction after flushing inrecirculation system. Research used experimental method with complete random design, consist of 4 treatments and 3 repetition. P1 used as control, P2, P3, P4 (depuration method in 8, 16, and 24 h). The flushing in 24 h was removed Pb 59%, from 0.66 ppm to 0.27 ppm. As this decline, the green mussels which was cultivated by fisherman will be more safety to consume as food products. The result of this depuration with recirculation system was lower and appropriate with BPOM standardization (2009), Perikanan (DKP) No:Kep 20/Men/2004,SK Ditjen POM No. 03725/B/SK/VII/1989, which the limit of pollutan in food products was 1.5 ppm